Relative bioavailability and comparative clinical efficacy of different ivermectin oral formulations in lambs - Suarez, Gonzalo (2013)
Several oral ivermectin (IVM) formulations for use in sheep are available in the pharmaceutical veterinary market in different countries. All of them are indicated at the same dose rate to treat the gastrointestinal nematodes. However, there is a lack of information on the relative systemic exposure (plasma bioavailability) and clinical efficacy among oral formulations routinely used in sheep. The main goal of the work reported here was to perform a pharmaco-parasitological assessment of three different IVM oral formulations in lambs infected with multiple resistant gastrointestinal nematodes. The comparative drug systemic exposure (IVM plasma concentrations) and nematodicidal efficacies (clinical efficacy) in lambs were determined for a reference (RF) and two different test (T1, T2) IVM oral formulations. One hundred and fifty six (n= 156) healthy Corriedale lambs, naturally infected with multiple resistant gastrointestinal nematodes were allocated into four experimental groups (n=39). Animals in each group received treatment (200 μg/kg) with either the RF, one of the test IVM formulations or were kept as untreated control. Blood samples were collected over 15 days post-treatment (n=8). The IVM plasma concentrations were measured by high performance liquid chromatography with fluorescence detection. The faecal nematode egg count reduction test (FECRT) and evaluation of the clinical efficacy were performed at day 14 post-treatment (n=6), where a predominance of IVM highly resistant nematodes was observed. Results and conclusions Neither the overall kinetic behaviour nor the IVM systemic exposure differed among all the tested oral formulations. Equivalent efficacy results were obtained for the different preparations, with an evident therapeutic failure to control Haemonchus spp. and Teladorsagia circumcincta, which correlates with a high degree of nematode resistance to IVM.